Retinal microvascular signs, cognitive function, and dementia in older persons: the Cardiovascular Health Study. - Baker, Michelle L; Marino Larsen, Emily K; Kuller, Lewis H; Klein, Ronald; Klein, Barbara E K; Siscovick, David S; Bernick, Charles; Manolio, Teri A; Wong, Tien Yin (Stroke, 2007)
BACKGROUND AND PURPOSE: Cerebral microvascular disease may be a risk factor for the development of dementia in elderly persons. We describe the association of retinal microvascular signs with cognitive function and dementia among older individuals. METHODS: In the population-based Cardiovascular Health Study, 2211 persons aged 69 to 97 years at recruitment had retinal photography. Photographs were evaluated for retinopathy (eg, microaneurysms, retinal hemorrhages), focal arteriolar narrowing, arteriovenous nicking, and retinal arteriolar and venular caliber. Cognitive status was determined from the Digit-Symbol Substitution Test and Modified Mini-Mental State Examination. Participants were also further evaluated for the presence of dementia with detailed neuropsychological testing. Persons with a prior stroke or taking antipsychotic or antidepressant medications were excluded. RESULTS: After adjusting for age, gender, race, field center, education level, internal carotid intima-media thickness, body mass index, hypertension, diabetes, and cigarette smoking status, persons with retinopathy had lower mean Digit-Symbol Substitution Test scores but not Modified Mini-Mental State Examination than those without retinopathy (39 versus 41, P=0.002). In hypertensive persons, retinopathy (multivariable-adjusted OR, 2.10; 95% CI, 1.04 to 4.24) and focal arteriolar narrowing (OR, 3.02; 95% CI, 1.51 to 6.02) were associated with dementia. These associations were not present in individuals without hypertension. CONCLUSIONS: In older persons, our study shows a modest cross-sectional association between retinopathy signs with poorer cognitive function and, in persons with hypertension, with dementia. These data support a possible role of cerebral microvascular disease in the pathogenesis of impaired cognitive function and dementia in older hypertensive persons.
Keywords: Aged; Aged, 80 and over; Cardiovascular Diseases; Cognition; Cross-Sectional Studies; Dementia; Female; Humans; Longitudinal Studies; Male; Microcirculation; Neuropsychological Tests; Retinal Vessels; Risk Factors

Microvascular and Macrovascular Abnormalities and Cognitive and Physical Function in Older Adults: Cardiovascular Health Study. - Kim, Dae Hyun; Grodstein, Francine; Newman, Anne B; Chaves, Paulo H M; Odden, Michelle C; Klein, Ronald; Sarnak, Mark J; Lipsitz, Lewis A (J Am Geriatr Soc, 2015)
OBJECTIVES: To evaluate and compare the associations between microvascular and macrovascular abnormalities and cognitive and physical function DESIGN: Cross-sectional analysis of the Cardiovascular Health Study (1998-1999). SETTING: Community. PARTICIPANTS: Individuals with available data on three or more of five microvascular abnormalities (brain, retina, kidney) and three or more of six macrovascular abnormalities (brain, carotid artery, heart, peripheral artery) (N = 2,452; mean age 79.5). MEASUREMENTS: Standardized composite scores derived from three cognitive tests (Modified Mini-Mental State Examination, Digit-Symbol Substitution Test, Trail-Making Test (TMT)) and three physical tests (gait speed, grip strength, 5-time sit to stand) RESULTS: Participants with high microvascular and macrovascular burden had worse cognitive (mean score difference = -0.30, 95% confidence interval (CI) = -0.37 to -0.24) and physical (mean score difference = -0.32, 95% CI = -0.38 to -0.26) function than those with low microvascular and macrovascular burden. Individuals with high microvascular burden alone had similarly lower scores than those with high macrovascular burden alone (cognitive function: -0.16, 95% CI = -0.24 to -0.08 vs -0.13, 95% CI = -0.20 to -0.06; physical function: -0.15, 95% CI = -0.22 to -0.08 vs -0.12, 95% CI = -0.18 to -0.06). Psychomotor speed and working memory, assessed using the TMT, were only impaired in the presence of high microvascular burden. Of the 11 vascular abnormalities considered, white matter hyperintensity, cystatin C-based glomerular filtration rate, large brain infarct, and ankle-arm index were independently associated with cognitive and physical function. CONCLUSION: Microvascular and macrovascular abnormalities assessed using noninvasive tests of the brain, kidney, and peripheral artery were independently associated with poor cognitive and physical function in older adults. Future research should evaluate the usefulness of these tests in prognostication.
Keywords: Aged; Aged, 80 and over; Cognition; Cross-Sectional Studies; Female; Humans; Male; Neuropsychological Tests; Vascular Malformations